δ13C of aromatic compounds in sediments, oils and atmospheric emissions: A review - Holman, A.; Grice, Kliti (Pergamon, 2018)
This review discusses major applications of stable carbon isotopic measurements of aromatic compounds, along with some specific technical aspects including purification of aromatic fractions for baseline separation. d13C measurements of organic matter (OM) in sediments and oils are routine in all fields of organic geochemistry, but they are predominantly done on saturated compounds. Aromatic compounds are important contributors to sedimentary organic matter, and provide indication of diagenetic processes, OM source, and thermal maturity. Studies have found evidence for a small13C-enrichment during diagenetic aromatisation of approximately 1–2‰, but the formation of polycyclic aromatic hydrocarbons (PAHs) from combustion and hydrothermal processes seems to produce no effect. Likewise, maturation and biodegradation also produce only small isotopic effects. An early application of d13C of aromatic compounds was in the classification of oil families by source. Bulk measurements have had some success in differentiating marine and terrigenous oils, but were not accurate in all settings. Compound-specific analyses measure certain aromatics with strong links to source, therefore allowing more accurate source identification. d13C measurements of individual aromatic compounds also allow identification of higher plant input in ancient sediments, even after severe diagenetic alteration or combustion to PAHs. Perylene, a PAH with a historically contentious origin, was assigned a source from wood-degrading fungi on the basis of its isotopic composition. Stable carbon isotopic measurements are also important in the analysis of organic matter from Chlorobiaceae, which is an important indicator of photic zone euxinic conditions in ancient sediments. A large range of aromatic products are formed from the carotenoid pigments of Chlorobiaceae, with an enriched carbon isotopic composition characteristic of the reverse tricarboxylic acid photosynthetic pathway employed by this family of organisms. In future, site-specific isotope analysis using techniques such as nuclear magnetic resonance spectrometry and high-resolution isotope ratio mass spectrometry may reveal more information about isotopic effects associated with aromatisation processes and maturation.